Outcomes Comparison of Direct Stenting Versus Pre-Dilation in Percutaneous Coronary Intervention - Aslam, Usman; Aslam, Soiba; Khan, Muhammad Fareed; Fahd Ur Rahman; Masoom, Muhammad; Muhammad Nadeem (Indus Journal of Bioscience Research, 2025)
Introduction: Percutaneous coronary intervention (PCI) is a standard treatment of coronary artery disease. Direct stenting versus pre-dilation is still a matter of clinical concern, particularly regarding the efficiency of the procedure and outcomes. Objective: To compare the clinical outcomes, safety, and procedural efficiency of direct stenting versus pre-dilation in patients undergoing PCI. Materials and Method: This is a prospective observational study conducted at Department of Interventional Cardiology, Armed Forces Institute of Cardiology / National Institute of Heart Diseases (AFIC/NIHD), Rawalpindi, Pakistan from December, 2024 to May, 2025. Two hundred patients undergoing PCI were randomly assigned to two groups direct stenting and pre-dilation. The baseline data, procedural factors, and 30-day outcomes were collected and analyzed. Findings: Direct stenting resulted in a lower contrast volume, a considerable reduction in procedure time, and a shorter fluoroscopy duration. The incidence of major adverse cardiac events was comparable between the two groups, but the minor vascular adverse events were less in the direct stenting group. Conclusion: Direct stenting is safe and an efficient procedure, which is an alternative to pre-dilation among properly identified PCI patients.